Devotion - Dillard, J. D.; Majors, Jonathan, 1989-; Powell, Glen; Jackson, Christina, (Actress); Sadoski, Thomas, 1976-; Kagasoff, Daren, 1987-; Jonas, Joe, 1989-; Neville, Spencer; Hargrove, Nick ([Place of publication not identified] : Paramount Studios, 2023)
Devotion, an aerial war epic based on the bestselling book of the same name, tells the harrowing true story of two elite US Navy fighter pilots during the Korean War. Their heroic sacrifices would ultimately make them the Navy's most celebrated wingmen.
New DVD 2023 Spring.